Altered microRNA expression and pre-mRNA splicing events reveal new mechanisms associated with early stage Mycobacterium avium subspecies paratuberculosis infection - Liang, Guanxiang (Sci Rep, 2016)
The molecular regulatory mechanisms of host responses to Mycobacterium avium subsp. paratuberculosis (MAP) infection during the early subclinical stage are still not clear. In this study, surgically isolated ileal segments in newborn calves (n = 5) were used to establish in vivo MAP infection adjacent to an uninfected control intestinal compartment. RNA-Seq was used to profile the whole transcriptome (mRNAs) and the microRNAome (miRNAs) of ileal tissues collected at one-month post-infection. The most related function of the differentially expressed mRNAs between infected and uninfected tissues was “proliferation of endothelial cells”, indicating that MAP infection may lead to the over-proliferation of endothelial cells. In addition, 46.2% of detected mRNAs displayed alternative splicing events. The pre-mRNA of two genes related to macrophage maturation (monocyte to macrophage differentiation-associated) and lysosome function (adenosine deaminase) showed differential alternative splicing events, suggesting that specific changes in the pre-mRNA splicing sites may be a mechanism by which MAP escapes host immune responses. Moreover, 9 miRNAs were differentially expressed after MAP infection. The integrated analysis of microRNAome and transcriptome revealed that these miRNAs might regulate host responses to MAP infection, such as “proliferation of endothelial cells” (bta-miR-196 b), “bacteria recognition” (bta-miR-146 b), and “regulation of the inflammatory response” (bta-miR-146 b).